Giant cell arteritis associated with acute Q fever – A case report. Issue 8 (August 2022) - Sarra, Evanthia; Mylonas, Charalampos C.; Tsekes, Georgios; Chochlakis, Dimosthenis; Psaroulaki, Anna; Chini, Maria
Abstract: Q fever is a worldwide spread zoonotic disease, caused by the gram-negative intracellular bacillus Coxiella burnetii . Apart from its most common manifestations, Q fever has been reported to occasionally mimic autoimmune diseases. We herein present a case of acute Q fever in a 69-year-old man, manifesting as prolonged fever with pneumonitis, in whom biopsy of the temporal artery revealed giant cell arteritis. Moreover, PCR testing of the biopsy specimen was positive for Coxiella burnetii, thus further supporting the possibly infectious etiology of some cases of biopsy proven giant cell arteritis, with implications for treatment.